2013
DOI: 10.1002/mop.27948
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of A Novel Dual Band‐Notched UWB Antenna by the Equivalent Circuit Model and Time Domain Characteristics

Abstract: In this article, a dual band‐notched ultrawideband (UWB) antenna is investigated by the equivalent circuit model and time domain characteristics. Transmission line model and L‐C resonant circuit model of the antenna are presented. Transfer function and pulse waveforms are also studied to evaluate the proposed antenna. Experimental results show that the proposed antenna meets the requirement of wide working bandwidth of 3.1–10.6 GHz with voltage‐standing wave ratio <2, while avoiding the interference from WiMAX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Moreover, it is also observed that the received signal amplitude is higher when two identical antennas are placed face-to-face (200 mV) with respect to side-by-side (100 mV) orientation. Overall ringing distortion is better than the existing UWB antennas in the literature [20]. To authenticate the similarity between received pulse S 2 (t) and transmitted or excited pulse S 1 (t) of the proposed antenna, the fidelity factor is calculated which is given as follows…”
Section: Time Domain Performancementioning
confidence: 99%
“…Moreover, it is also observed that the received signal amplitude is higher when two identical antennas are placed face-to-face (200 mV) with respect to side-by-side (100 mV) orientation. Overall ringing distortion is better than the existing UWB antennas in the literature [20]. To authenticate the similarity between received pulse S 2 (t) and transmitted or excited pulse S 1 (t) of the proposed antenna, the fidelity factor is calculated which is given as follows…”
Section: Time Domain Performancementioning
confidence: 99%
“…An equivalent distributed element circuit can be used to study the performance of UWB antenna . In Figure (a) the T‐shape slots and the CSRRs can be seen as two series stub in a transmission line.…”
Section: Equivalent Circuit Modelmentioning
confidence: 99%
“…Thus, the radiation is very low at these two notched frequencies and dual band-notched is achieved. An equivalent distributed element circuit can be used to study the performance of UWB antenna [12][13][14]. In Figure 3(a) the T-shape slots and the CSRRs can be seen as two series stub [13] in a transmission line.…”
Section: Transmission Line Model Analysismentioning
confidence: 99%
“…Lot of techniques have been reported in the literature to achieve band notched characteristics in the range of UWB at different standard narrow bands. Some of them used half wavelength slots/slits on the main radiating patch of different shapes , open ended quarter wavelength slots/slits or stubs on main radiating element or on ground plane , parasitic elements near radiating patch or feed line , and segmented patch . Some new concepts are also mentioned which utilize metamaterial like structures and EBG structures .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of band notched characteristics in UWB antennas can be explained using conceptual lumped RLC equivalent circuit analysis as proposed in literature . The conceptual equivalent RLC resonant circuit diagrams are based on the resonances occurred at the notched bands.…”
Section: Introductionmentioning
confidence: 99%